Assessing the Influence of the Media Technologies on Communication Practices and Social Change - Yadima, Gaius Jeff; Iliya, Silas (Lembaga Yasin AlSys, 2025)
This paper investigates the impact of media technologies on communication practices and social change through the framework of technological determinism. The purpose of the study is to analyze how advancements in media technologies influence individual and societal communication, thereby affecting cultural norms, political engagement, and economic development. Employing a qualitative descriptive methodology, this research evaluates both the positive and negative consequences of media technology adoption. The findings reveal that while technological determinism posits that technology fundamentally shapes social structures and behaviors, there is also significant evidence supporting the role of human agency in mediating media use. This dual perspective emphasizes the complexity of the relationship between technology and society, suggesting that media technologies not only drive societal transformation but also interact with human choices and cultural contexts. The implications of this study highlight the necessity for scholars and practitioners to adopt a nuanced understanding of media technologies' influence, encouraging further research that integrates both technological impacts and human agency. Ultimately, this research contributes to the broader discourse on the interplay between technology and society, underscoring the importance of critically examining the role of media in shaping communication practices and fostering social change.